Synthesis of xylitol from meranti wood sawdust in batch process by locally produced xylose reductase - Islam, S. M. Rafiqul (2012)
The microbial production of xylitol has been studied extensively as an alternative to the chemical process, which on an industrial-scale is time-consuming mainly due to sterilization, inoculum development and product recovery problem. Apart from using pure xylose, no other substrate has been proposed for xylitol synthesis using xylose reductase (XR). The aim of this study was to synthesize xylitol, a specialty product, from Meranti wood sawdust hemicellulosic hydrolysate (MWSHH) by locally produced XR. MWS is a sawmill waste, which can be a promising source of xylose for xylitol production. The kinetic parameters of mathematical models were determined to predict xylose, glucose, furfural, and acetic acid concentration in the hydrolysate. Optimization of MWS hydrolysis was conducted with statistical design including onefactor-at-a-time (OFAT) method for maximum xylose recovery. The results of OFAT indicated the residence time, temperature, and acid concentration to be the major factors improving xylose recovery with a value of 60 min, 125 ºC, and 4%, respectively. These factors were further optimized by response surface methodology (RSM), and the optimum values obtained were 80 min, 124 ºC, and 3.26%, respectively. Under these conditions xylose yield and selectivity were attained at 90.6% and 4.05 g/g, respectively. XR was isolated from adapted C. tropicalis and characterized. The activity of NADPH-dependent XR measured was 11.16 U/mL. It was stable at pH 5.0–7.0 and temperature of 25–40 ºC for 24 h, and retained above 95% of its original activity after 4 months of storage at –80 ºC. The K values of XR for xylose and NADPH were 81.78 mM and 7.29 µM while the Vmaxm for xylose and NADPH were 178.57 and 12.5 µM/min, respectively. The high V max and low K values of XR for xylose reflecting a highly productive reaction among XR and xylose. Further, a sequential optimization based on OFAT approach and statistical program was followed to enhance xylitol production from xylose-rich MWSHH using XR. Firstly, the OFAT method coarsely evaluated the optimum levels of variables. Secondly, the significant variables for maximum xylitol production were screened out through fractional factorial design (FFD) to be reaction time, temperature and pH. Finally, the significant variables were fine-tuned by RSM and were found to be 12.25 h, 35 ºC and 6.5, respectively, giving the maximum xylitol yield and productivity of 86.57% and 1.33 g/L· h, respectively. Optimization of process conditions using sequential strategies resulted in 1.55-fold improvement in overall xylitol synthesis. This study developed a novel reaction medium to improve xylitol production to a considerable level using MWSHH.